‘Suck more piss’: how the confluence of key Melbourne-based audiences, musicians, and iconic scene spaces informed the Oz rock identity - Oldham, Paul (Perfect Beat, 2014)
Australian pub rock began in Melbourne in late 1969/early 1970 and became the nation’s most successful penetration into the international rock market and audiences. While commendable work has been written about Australia’s scene spaces (particularly Homan 2003; Stratton 2007), most remain Sydney-centric and typically overlook the equally (if not more) important Melbourne rock scene. In all cases the fermentative period of pub rock—and especially the combined roles played by its early audiences, musicians and venues—remains under-examined. This article will explore Australian pub rock’s beginnings through the lens of the career trajectory of Billy Thorpe & The Aztecs, and how that influenced, and was influenced by, the specific demands of Melbourne’s fluid audiences and venues leading up to the Oz rock era, using the key case studies of Mulgrave’s Village Green Hotel and Nunawadings’s Whitehorse Hotel.